Investigating the Causal Linkage among Economic Growth, Energy Consumption, Urbanization and Environmental Quality in ASEAN-5 Countries - Batool, Syeda Azra; Ahmad, Humara; Gillani, Syed Muhammad Ahmad Hassan; Raza, Hamad; Siddique, Muhammad; Khan, Nohman; Qureshi, Muhammad Imran (International Journal of Energy Economics and Policy, 2021)
The present study aims to explore the causal relationship among economic growth energy consumption and urbanization and environmental quality in ASEAN-5 countries. The current study conduct time series analysis in ASEAN-5 countries using the granger casualty model consisting data set from 1980 to 2018. The outcomes of the present study reveals that the energy consumption urban population granger cause to CO2 emission in ASEAN-5 countries. The study suggested that ASEAN-5 should reduce the utilization of fossil fuel based energy and induct robust policies towards augmenting the adeptness of renewable energy and energy-usage programs to condense redundant energy waste. Keywords: Economic growth, energy consumption, environmental quality, CO2 emission, environmental sustainability, ASEAN-5 JEL Classifications: F64, N75, O13 DOI: https://doi.org/10.32479/ijeep.11213